The Effect of The Implementation of Peer Tutoring Learning in Improving The Results of Learning in Reading The Quran of Students at UPT SMAN 9 Bulukumba - Mustang. H (Universitas Islam Negeri Alauddin, 2024)
The objectives of this study are: 1) to describe how students of UPT SMAN 9 Bulukumba learn to read the Qur'an through peer coaching. 2) to describe the learning objectives for students of UPT SMAN 9 Bulukumba who like to read the Qur'an. 3) to evaluate how parental guidance improves students' knowledge in reading the Qur'an at UPT SMAN 9 Bulukumba. This study uses the perspective of religious psychology, educational psychology and normative psychology and is a quantitative research design, for example post facto. The instruments used in this study were surveys and learning outcome tests. Simple linear regression analysis was used for inferential data analysis and descriptive data analysis. The following are the results of the study: 1) The peer teaching approach to students is included in the moderate category with a percentage of 66% and an average value of 68.79. 2) The average value is 86.82 and the percentage of students who successfully learn to read the Qur'an is included in the good category. 3) Student learning outcomes in reading the Qur'an (Y) at SMAN 9 Bulukumba are significantly influenced by the peer teaching learning strategy (X) with a t value of 6.799 and a significance value of 0.000. Based on the results of the study, teachers can teach students how to read and understand the Qur'an by using the peer tutoring method as an alternative method.